The Role of Intelligent Leadership in Developing a Culture of Excellence an Analytical Study for the Opinion of Managers in the Traffic Directorate, Erbil ffiliate to the Ministry of the Interior - Sartip Abdullah Wahid; Mahabat Noori Abdullah (Zanco Journal of Humanity Sciences)
This research aims to analyze the relationship and influence of intelligent leadership for directorates of the traffic directorate in the city of Erbil represented (sharing the vision and common goals, social intelligence, rational intelligence) in the dimensions of the culture of excellence and represented (basic competencies, social responsibility, work value). Represents the general framework for researching the research problem with its represents several questions about the nature of the relationship and influence and the contrast between independent variable (Intelligent leadership ) and dependent variable ( Excellence of culture) .A research hypothesis was designed to express main hypotheses , to be sure from the validity of the hypotheses all of them underwent for multiple tests , the search was used questionnaire form as a way to collect data , and it was distributed to ( 130) managers and its represent (15) departments and directorates , it were retrieved (125) forms valid for analysis . The research adopted the descriptive and analytical approach, through the application of statistical methods by using program (SPSS V.22). The research has reached a number of conclusions the most important of them is having a relationship positive incorporeal correlation, this indicates whenever adopted the mentioned organization on intelligent leadership it can to developing a culture of excellence. And the research suggested the necessity of investing in strong relationships between the main and sub-variables at the macro and micro level and direct it to the service of the aforementioned organization.